Important Characteristics to Become Autonomous Learner - Umaralieva Munojat Mashrabovna; Yakhyoyeva Sarvinoz Khayotjon kizi (Research Parks Publishing LLC, 2022)
This article focuses on the importance of teaching students to independent learning which can make learners motivated to take responsibility for their learning and working with teachers. This paper also analyzes the specific features of independent learners which are vitally necessary to become an autonomous learner. In terms of students` self-education, there are a myriad of points of view on this topic. Since the topic of independent learning is a very broad topic, each idea related to this topic has it`s own specific evidence. In the view of the progress made in the field of education, the holders of every idea related to this topic came to this consideration that independent learning is very useful in the field of education and also for students.